BACTERIAL AETIOLOGY OF OSTEOMYELITIS CASES AT FOUR HOSPITALS OF LAHORE - Malik, Faria (Journal of Ayub Medical College Abbottabad, 2003)
Background: The conclusive diagnosis of osteomyelitis requires isolation of pathogen in aspirate from bone lesion, bone debridement and blood culture. The present research was undertaken to study the microbiological pattern of cases of osteomyelitis reporting to four hospitals in Lahore. Method: One hundred and fifty patients of osteomyelitis were selected from outpatient departments and Orthopaedic wards of Lahore General Hospital, Sir Ganga Ram Hospital, Services Hospital and Mayo Hospital, Lahore. Specimens of pus from bone, blood and bone debridement were collected. All samples were inoculated onto two Blood Agar and one MacConkey agar plates. One Blood Agar plate was incubated anaerobically for 48 hours and the other two plates aerobically for 24 hours. Smears were made from samples and stained by the Gram’s stain. The colonies obtained were processed according to the technique of Mackie and MacCartney.Results: The commonest isolates belonged to the Enterobacteriaceae (32.8%), followed by Staphylococcus aureus (29.5%), Pseudomonas aeruginosa (15.5%), anaerobes (2.6%) and miscellaneous (19.3%). Five (2.7%) anerobic bacteria were isolated. Anaerobic bacteria were peptostreptococci, peptococci and bacteroides either alone or as a mixed infection. Conclusion: The present study highlights the importance of microbiological examination of bone in cases of osteomyelitis. Different types of bacteria either alone or as a mixed infection could be the causative agent(s). Key Words: Bacteria, Aerobes, Staphylococci, Enterobacteriaceae, Pseudomonas, Anaerobes, Osteomyelitis.